The Importance of the Team in Project Management - Usmanova Yulduzxon (Genius Journals, 2022)
Creating an effective project team is one of the main problems faced by businesses all over the world. As you know, the success of the project is influenced by many different factors: financial, time resources, the uniqueness of the project, as well as an experienced, highly qualified team of specialists. Today, in the era of the strongest global competition and the emergence of the latest technologies, teamwork plays a leading role in achieving tangible organizational results, contributes to maintaining the competitive advantages of companies and their efficiency. The relevance of the chosen topic is because effective project management is of particular importance due to the rational formation of the project team.
Keywords: team; project management; project team; effective project team